Serum miRNA Signature in Rheumatoid Arthritis and “At-Risk Individuals” - Cunningham, Clare C.; Wade, Sarah; Floudas, Achilleas; Orr, Carl; McGarry, Trudy; Wade, Siobhan; Cregan, Sian; Fearon, Ursula; Veale, Douglas J. (Frontiers in Immunology, 2021)
Background MicroRNAs (miRNAs) are small non-coding RNAs which have been implicated as potential biomarkers or therapeutic targets in autoimmune diseases. This study examines circulatory miRNAs in RA patients and further investigates if a serum miRNA signature precedes clinical manifestations of disease in arthralgia or “at-risk individuals”. Methods Serum was collected from HC subjects (N = 20), RA patients (N = 50), and arthralgia subjects (N = 10), in addition to a subgroup of the RA patients post-methotrexate (MTX) (N = 18). The FirePlex miRNA Immunology-V2 panel was selected for multiplex analysis of 68 miRNAs in each sample. DNA intelligent analysis (DIANA)-mirPath and Ingenuity Pathway Analysis (IPA) software were used to predict pathways targeted by the dysregulated miRNAs. Results 8 miRNA (miR-126-3p, let-7d-5p, miR-431-3p, miR-221-3p, miR-24-3p, miR-130a-3p, miR-339-5p, let-7i-5p) were significantly elevated in RA serum compared to HC (all p < 0.01) and 1 miRNA (miR-17-5p) was significantly lower in RA (p < 0.01). High specificity and sensitivity were determined by receiver operating characteristic (ROC) curve analysis. Both miR-339-5p and let-7i-5p were significantly reduced post-MTX (both p < 0.01). MiR-126-3p, let-7d-5p, miR-431-3p, miR-221-3p, miR-24-3p, miR-130a-3p were also significantly elevated in subjects “at risk” of developing RA (all p < 0.05) compared to HC. IPA analysis of this miRNA signature identified downstream targets including key transcription factors NF-κB, STAT-1, STAT-3, cytokines IL-1β, TNF-α, and matrix-metalloproteases all importantly associated with RA pathogenesis. Conclusion This study identified six miRNAs that are altered in both RA and “at-risk individuals,” which potentially regulate key downstream pathways involved in regulating inflammation. These may have potential as predictive signature for disease onset and early progression.